2020
DOI: 10.4314/ijbcs.v14i6.25
|View full text |Cite
|
Sign up to set email alerts
|

Profils morpho-biometriques de la poule locale du Burkina Faso

Abstract: Au Burkina Faso les informations sur la poule locale sont rares entrainant des difficultés objectives de son exploitation rationnelle. Un total de 948 individus (692 femelles et 256 mâles) provenant de 251 élevages reparties dans les 3 zones agro-écologiques du Burkina Faso a été évalué pour 13 traits corporels quantitatifs et 09 qualitatifs dans le but de caractériser la variabilité phénotypique de la poule locale. Il ressort 13 coloris de plumage avec le blanc (19,16%) et l’herminé (16,75%) comme couleurs do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
(8 reference statements)
1
4
2
Order By: Relevance
“…Two dominant feather types such as smooth feathers (wild type) and curly feathers (locus F) were identified. These results were different from those obtained in Burkina Faso 10 . The dominant (smooth) plumage of chicken in this study was found to be under the control of the f+ allele (f+*f+/f+*f+: wild type) 26 .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Two dominant feather types such as smooth feathers (wild type) and curly feathers (locus F) were identified. These results were different from those obtained in Burkina Faso 10 . The dominant (smooth) plumage of chicken in this study was found to be under the control of the f+ allele (f+*f+/f+*f+: wild type) 26 .…”
Section: Discussioncontrasting
confidence: 99%
“…Chicken from the Centre-North and South-West regions were more similar in their characteristics resulting in an intermediate sub-population between the Konde and Sahel chickens. In the current study, three populations were identified in contrast to a previous study conducted by Pinde et al10 who found only two subpopulations. This difference in the number of sub-populations may be due to the difference in the sample sizes of the Konde chicken between these two studies.…”
contrasting
confidence: 99%
See 3 more Smart Citations